Robô móvel para inspeção de materiais perigosos - Holtman, Murilo Santos (2012)
Several tasks that require the handling of potentially dangerous objects or the exposure of humans to life-threatening conditions, such as explosive disposal, may be carried out with the aid of remotely controlled electromechanical devices, or robots. The costs of such equipment, however, are often in the tens of thousands of dollars. The goal of this work is to therefore develop the mechanics and electronics (hardware and software) of a low-cost, compact mobile robot that may be employed in such situations and be remotely controlled by a human user. The project is to be carried out with the following steps: firstly, technical analyses and decisions are made; next, the robot’s mechanics are designed and built; embedded and remote control electronics are then developed; and lastly, testing and documentation take place. The intended result is a simple and adaptable platform that lends itself to demonstrating the feasibility of building such mobile robotic systems with a cost under R$ 1000 (around US$ 500).